DATA QUALITY AWARENESS UNTUK MINIMALISASI RISIKO DAN MAKSIMALISASI STAKEHOLDER VALUE - Harmadji, Dwi Ekasari (Fakultas Ekonomi Universitas Wisnuwardhana, 2015)
The main objective of this research to improve Data QualityAwareness in all sub-unit employees work at the time of first input datainto the system that must be filled in correctly and completely to allmandatory fields. Through interpretive qualitative research, this studyusing stakeholder theory, which is considering the position of thestakeholders who are considered powerful than just a shareholderposition only. Results of this study indicate that there is a direct linkwith increased awareness of data quality will minimize risk andmaximize stakeholder value.Keywords: Data Quality Awareness, risk, stakeholder theory